2014
DOI: 10.1038/ncomms4639
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory projectome in the zebrafish forebrain revealed by genetic single-neuron labelling

Abstract: Chemotopic odour representations in the olfactory bulb are transferred to multiple forebrain areas and translated into appropriate output responses. However, a comprehensive projection map of bulbar output neurons at single-axon resolution is lacking in vertebrates. Here we unravel a projectome of the zebrafish olfactory bulb through genetic single-neuron tracing and image registration. We show that five major target regions receive distinct modes of projections from olfactory bulb glomeruli. The central porti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
111
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(124 citation statements)
references
References 59 publications
13
111
0
Order By: Relevance
“…Within the Dp, the large core region samples intermingled inputs from all the glomerular clusters ( Fig. 5.4), thus transforming topographic information in the OB to broad and sparse representations (Miyasaka et al 2014). An optical imaging study showed that individual Dp neurons extract information about discrete combinations of odorant molecular features from ensembles of glomeruli to establish representations of higher-order olfactory objects ).…”
Section: Posterior Zone Of the Dorsal Telencephalon (Dp)mentioning
confidence: 98%
See 2 more Smart Citations
“…Within the Dp, the large core region samples intermingled inputs from all the glomerular clusters ( Fig. 5.4), thus transforming topographic information in the OB to broad and sparse representations (Miyasaka et al 2014). An optical imaging study showed that individual Dp neurons extract information about discrete combinations of odorant molecular features from ensembles of glomeruli to establish representations of higher-order olfactory objects ).…”
Section: Posterior Zone Of the Dorsal Telencephalon (Dp)mentioning
confidence: 98%
“…However, physiological and anatomical studies have begun to shed light on basic principles of odor information representation and computation in the secondary olfactory circuitry of zebrafish Miyasaka et al 2009;Blumhagen et al 2011). In particular, the most recent study combining a genetic single-neuron labeling method with the image registration system has uncovered a nearly comprehensive axon projection map from the OB to higher bran centers in zebrafish larvae (Miyasaka et al 2014).…”
Section: Higher Olfactory Centersmentioning
confidence: 99%
See 1 more Smart Citation
“…The olfactory system is an attractive model for the study of axon targeting because each olfactory sensory neuron (OSN) assumes a specific identity as it chooses a single odorant receptor (OR) from a large gene repertoire and since OR choice is closely coordinated with axonal targeting (Alioto and Ngai, 2005;Zhang and Firestein, 2002). Although sensory neurons expressing a particular OR are broadly dispersed in the olfactory epithelium (OE), their axons converge upon one or a few reproducibly located OR-specific glomeruli in the olfactory bulb (OB); there, they synapse with the dendrites of second order neurons that communicate olfactory information deeper into the brain (Ramon y Cajal, 1892;Ressler et al, 1994;Vassar et al, 1994;Mombaerts et al, 1996;Sosulski et al, 2011;Miyasaka et al, 2014). The OR-specific glomerular map relates odorant experience to neuronal activity at specific locations within the OB, providing a basis for the identification and discrimination of odorants (Bozza et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Such restricted sub-compartmentalization within a glomerulus has been observed both in mammals (Treloar et al, 1996) and fish (Friedrich and Korsching, 1998), implying functional segregation within the glomeruli. Thus, the re-sorting concept of efferent axons to the telencephalon (Miyasaka et al, 2014) might be established at the site of olfactory glomeruli, as shown by the present study.…”
Section: Discussionmentioning
confidence: 49%